2021
DOI: 10.3390/mi12050554
|View full text |Cite
|
Sign up to set email alerts
|

Editorial for the Special Issue on Micro-Electro Discharge Machining: Principles, Recent Advancements and Applications

Abstract: Micro Electrical Discharge Machining (micro-EDM) is a thermo-electric and contactless process most suited for micro-manufacturing and high-precision machining, especially when difficult-to-cut materials, such as super alloys, composites, and electro conductive ceramics, are processed [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The development of micro and nano systems, driven by technological progress [51,52], has a notable impact on EDM. Specifically, micro electrical discharge machining (MEDM) plays a crucial role in creating microstructures [53,54]. MEDM technology incorporates various processing methods, including wire [55,56], sinking [54,57], drilling [48,53], and milling [47,58].…”
Section: Electrical Discharge Coating (Edc) Is An Unconventional Tech...mentioning
confidence: 99%
See 2 more Smart Citations
“…The development of micro and nano systems, driven by technological progress [51,52], has a notable impact on EDM. Specifically, micro electrical discharge machining (MEDM) plays a crucial role in creating microstructures [53,54]. MEDM technology incorporates various processing methods, including wire [55,56], sinking [54,57], drilling [48,53], and milling [47,58].…”
Section: Electrical Discharge Coating (Edc) Is An Unconventional Tech...mentioning
confidence: 99%
“…The EDM process involves a wide range of phenomena, such as phase transitions [79][80][81], melt behavior [82][83][84], oxidation [36,50,85], residual stresses [86][87][88][89][90], energy transfer, absorption and dissipation [91][92][93][94], chemical reactions [75,95], microstructural changes [53,81,96], etc. The EDM process is generally based on the melting and evaporation of material under the influence of highly concentrated electrical energy, which is converted into thermal energy.…”
Section: Edm Process Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that EDM has the supremacy to machine hard-to-cut alloys, composites, and tough metals without introducing changes in their metallurgical characteristics [ 12 ]. EDM is a spark erosion process; as previously said, a succession of recurring sparks is used between the tool and the workpiece [ 13 ], which erodes the material from the workpiece by worsening the melting and vaporization. In order to create a discharge gap between the tool and the workpiece, the electrode, and the workpiece are submerged in the dielectric fluid, which is then ionized by the sparks that are continuously passing through it [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic energy of ions and electrons' affects the workpiece's surface, causing the tool to generate thermal energy. The temperature rises to 10,000 • C in milliseconds due to the strong localised heat flow [15]. When the temperature reaches an extreme level in one area, it vaporises the material and removes some melting metals in the form of particles.…”
Section: Introductionmentioning
confidence: 99%